2020
DOI: 10.1590/1984-0462/2020/38/2018262
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder: A Systematic Review About Nutritional Interventions

Abstract: Objective: To identify and analyze the scientific evidence of nutritional interventions performed in children and adolescents with Autism Spectrum Disorder. Data sources: A systematic review was conducted in the MEDLINE, Cochrane Library, Embase, LILACS, Google Scholar, PubMed, PsycINFO and Periódicos CAPES databases, using a search strategy to identify studies published between January 2003 and March 2018, in Portuguese, English and Spanish. Were included studies that described nutritional interventions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
0
20
1
3
Order By: Relevance
“…Evidence shows that in a sizeable proportion of individuals with ASD, the dietary intervention is a form of complementary and alternative medicine, i.e., practices and products that are not part of conventional Western medical care [ 51 ]. Implementation of a GFCF (gluten-free/casein-free) diet is the most used dietary intervention in ASD [ 23 , 52 ]. It is based on the “opioid excess hypothesis”.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence shows that in a sizeable proportion of individuals with ASD, the dietary intervention is a form of complementary and alternative medicine, i.e., practices and products that are not part of conventional Western medical care [ 51 ]. Implementation of a GFCF (gluten-free/casein-free) diet is the most used dietary intervention in ASD [ 23 , 52 ]. It is based on the “opioid excess hypothesis”.…”
Section: Discussionmentioning
confidence: 99%
“…It postulates that ASD results from a metabolic disorder in which opioid peptides produced by metabolism of gluten and casein pass through an abnormally permeable intestinal wall into blood, and exert harmful effects on processes in the brain [ 52 ]. Although scientific evidence shows some improvements in behavior on GFCF diet, there is insufficient data to support its broader use [ 23 , 53 ]. Several caregivers of our ASD subjects reported that they rather reduced than fully eliminated either gluten or casein, which raises questions about efficacy of such “partial” dietary treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These 2 RCT demonstrated significant improvements in social isolation, and the overall ability to communicate and interact among ASD children. 31 However, the number of studies were insufficient to conclude the effect of a GCFD. The most recent review included studies between 2003 and 2019 with a total of 9 RCT with ages ranging between 2 to 18 years and the duration ranging from a week to 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Autism Spectrum Disorder (ASD), considered one of the psychiatric or mental disorders, is characterized by an early onset neurological development disorder, impairment of social and communication skills. ASD covers autistic disorder (autism), Rett syndrome, Asperger's disorder, childhood disintegrative disorder, and pervasive developmental disorder not otherwise specified (Monteiro et al, 2020). ASD has a multifactorial cause, that is, genetic and environmental factors are involved.…”
Section: Introductionmentioning
confidence: 99%